TRANSLATION AND VALIDATION OF THE HEALTHCARE TEAMWORK SURVEY QUESTIONNAIRE:STUDY DESIGN FOR THE MALAYSIAN CONTEXT - W.S., Wan Siti Auni; D.J., Pereira; P.Y., Lim; H., Sakinah (2017)
Cross-professional teamwork in healthcare is necessary to support integrated service delivery. However, cross-professional teamwork has not been given sufficient attention in developing country contexts. This paper presents a study design for translating and validating a teamwork survey questionnaire (TSQ) for the Malaysian context. The original TSQ was previously used in a developed country context. The tool will be translated into Malay which is the national language of Malaysia. Survey data will be subject to exploratory factor analysis to assess construct validity and Cronbach’s alpha test for reliability. The forward-backward translation approach of cross-cultural adaptation will be utilized. Two independent translators shall initially translate the questionnaire before reconciliation by the research team. The reconciled Malay version will then be back-translated into English. English translation will be contrasted against the original TSQ for further accuracy improvements in the Malay version. Face validation will be conducted with five academicians and five healthcare professionals to obtain feedback on necessary further adjustments. Upon finalizing the Malay version TSQ, interviews with service managers and senior healthcare professionals will be conducted to identify services with cross-professional teamwork at a designated hospital. A total of 150 respondents for survey validation will be recruited from identified services within the hospital. Different healthcare professionals having cross-communication and sharing patient care objectives will meet the criteria for a cross-professional team service. The validated Malay version TSQ could provide an invaluable tool for the assessment and improvement of cross-professional teamwork in the Malaysian healthcare context.